Interaksi Mahasiswa pada Pembelajaran Jarak Jauh - Arnani, Ni Putu Rizky; Fitri, Arrumaisha (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Distance education has become an alternative during the pandemic, from traditional learning, face-to-face with information and technology to help bridge the separation of distance and time between teachers and students to build interaction during the learning process. The purpose of this study was to get an overview of interactions in online teaching in terms of gender. The research was descriptive quantitative. The sampling technique used purposive sampling with 380 students as participants. Research instrument used interaction scale consists of four aspects such as student-student interaction, student-student interaction with content, student-instructor interaction, and student-student interaction with technology. The data analysis technique uses descriptive statistics. The results showed that student interaction was in the moderate category (70.5%). Interaction with technology sub-component shows the least amount in the low category compared to the other sub-components. Based on gender, there are differences in student interactions in online learning between female and male students. Apart from that, the average interaction between female students has a higher average than male students.